Blood of the hunters - Compton, Ralph; Rovin, Jeff (The gunfighter series, 2020)
"John Stockbridge was once a peaceful man of medicine. Now, he's better known as Dr. Vengeance, a man who is as fast with a shotgun as any other gunfighter is with a six-gun. The murders of his wife and child left him with an aching hole where his soul once was. His only solace comes from wandering the West. Along the way, he encounters a woman and her two children searching for their missing fur-trapper husband/father in the Rockies. In the process, they run afoul of some foul former Confederates who have amassed money and local power by robbing those traveling west through a mountain pass. While searching for the missing trapper--and aided by a Mexican mountain man and an independent woman who works at the local hotel--Stockbridge must take down the vicious highwaymen one by one."--Back cover.